REKRUTMEN TERBUKA JABATAN PIMPINAN TINGGI PADA BADAN KEPEGAWAIAN DAERAH KOTA BANDUNG - Mia Rosmiati; Asep Sumaryana; AD. Saefullah; Ahmad Buchari (Jurnal Administrasi Publik, 2018)
This article is the result from dissertation research about open recruitment. Indonesia has been running several methods in employee‟s selection . According to UU No. 5 Year 2014 on State Civil Apparatus (ASN), in order to get a competent employee based on merit system, all district should held the open recruitment system. The purpose of this study is to determine the implementation of open recruitment for Leader Position (JPT) Pratama in BKD Bandung. Open recruitment conducted by the government of Bandung with BKD as an organizer institution, is part of a merit system where the aim is to obtain candidate who will headed an institution with competence, based on the existing rules in merit system.. But the fact showed there are still many things that have not been as expected. The method used is qualitative research design where in this study the author seeks to observe and reveal in depth what is happening in the field and will be more observed and explored the behavior of the object under investigation which includes examining the process undertaken by the Agency Bandung Regional Personnel who have implemented an open recruitment system. The results of this study indicate that some problems appeared as the findings of this research. The conclusion of this research is the implementation of open recruitment in Bandung city has been running well but there are some inputs that the author suggest as a recommendation to the government of Bandung in order to forwards the implementation of this open recruitment system can do more better.Keywords: Open Recruitment, Competent, Merit System